SAR distribution in a bio-medium in close proximity with dual segment cylindrical dielectric resonator antenna - Gangwar R.K.; Singh S.P.; Kumar D. (My University, 2025)
This paper reports simulation and experimental studies of input characteristics of a dual segment cylindrical dielectric resonator antenna (DSCDRA) in free space and in the presence of a bio-medium (synthetic muscle) along with specific absorption rate (SAR) distribution in the synthetic muscle medium due to the antenna at microwave frequencies. The simulation study has been carried out using CST Microwave Studio software. The experimental SAR distribution has been obtained using two 50 L-shaped and straight coaxial probes and Agilent 3 Hz50 GHz spectrum analyser. The experimental results for variation in return loss versus frequency for the DSCDRA and SAR distribution in synthetic muscle medium due to the antenna are compared with simulated results. © 2012 Informa UK, Ltd.